THE IMPORTANCE OF THE ARABIC LANGUAGE ENVIRONMENT TO IMPROVE THE ABILITY OF STUDENTS TO SPEAK ARABIC AT IAI AL-KHAIRAT PAMEKASAN - Afandi, Afandi (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to describe the phenomenon of the Arabic language environment on campus and analyze its influence on the improvement of speaking skills (maharah al-kalam) of students of the Arabic Language Education Study Program. This study uses a qualitative descriptive approach with a location in one of the Islamic universities in Java. The research subjects consisted of 25 fourth-semester students, two language coaches, and one coordinator of the language environment program. Data was collected through observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman's interactive model, which included data reduction, data presentation, and conclusions drawn. The validity of the data is strengthened through triangulation of sources and techniques. The results of the study show that the Arabic language environment on campus has a significant impact on improving students' speaking skills. Activities such as Arabic Day, muhadatsah, and nadi al-lughah increase confidence, fluency in speaking, and the accuracy of students' language structure. However, several obstacles were found such as the lack of discipline in the use of Arabic and the lack of supporting facilities. Overall, this study confirms that a consistently designed language environment can create a communicative, interactive, and effective learning atmosphere in improving students' speaking skills.